2021
DOI: 10.1002/qre.2957
|View full text |Cite
|
Sign up to set email alerts
|

Predictive monitoring using machine learning algorithms and a real‐life example on schizophrenia

Abstract: Predictive process monitoring aims to produce early warnings of unwanted events. We consider the use of the machine learning method extreme gradient boosting as the forecasting model in predictive monitoring. A tuning algorithm is proposed as the signaling method to produce a required false alarm rate. We demonstrate the procedure using a unique data set on mental health in the Netherlands. The goal of this application is to support healthcare workers in identifying the risk of a mental health crisis in people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
0
10
0
5
Order By: Relevance
“…The XGBoost algorithm has been successfully used for a wide range of medical applications, including disease diagnosis, survival estimation, outcomes, prognosis, drug research and development. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The XGBoost algorithm has been successfully used for a wide range of medical applications, including disease diagnosis, survival estimation, outcomes, prognosis, drug research and development. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The XGBoost algorithm has been successfully used for a wide range of medical applications, including disease diagnosis, survival estimation, outcomes, prognosis, drug research and development. 38 XGBoost was created by Chen and Guestrin 39 as an ensemble of multiple decision trees. Decision trees are a robust ML model capable of a high degree of accuracy and interpretability.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…As mentioned in the main text, the original algorithm proposed by Huberts et al 13 is altered to accommodate our particular dataset characteristics and for comparison purposes. It should be noted that these alterations may not be suitable for other situations; in their study, the algorithm in its original set-up showed good performance.…”
Section: Appendix B: Adaptations Of Original CV Algorithmmentioning
confidence: 99%
“…After obtaining the threshold, a new model is fitted on the entire training set for prediction on the test set. The set-up is based on the work by Huberts et al 13 ; for changes made to the original algorithm, we refer to Appendix B. Let 𝐹𝐴𝑅 𝑣𝑎𝑙 be defined as the FAR obtained on the internal validation set.…”
Section: Split Samplementioning
confidence: 99%
See 1 more Smart Citation